A gazdasági átalakulás és következményei Magyarországon (1988-1998) - Domonkos, Endre (Közép-Európai Közlemények, 2023)
Economic transition in Hungary was coupled with the adoption of the “Companies Act” in October 1988, which made it possible to state enterprises to convert themselves either into private company or public limited liability company. This led to the collapse of the socialised sector and paved the way towards the creation of a market economy. Liberalisation programme started on 1 January 1989, which abolished all restrictions on wages and prices. Measures were also introduced for liberalising import. The first wave of privatization was uncontrolled, which was placed under the direct supervision of the state in the autumn of 1990 by the coalition government led by the Hungarian Democratic Forum. The main objective of the conservative cabinet was to promote the emergence of a new Hungarian entrepreneur stratum. From 1994 privatisation strategy was changed by the Socialist-Liberal government, which encouraged bigger participation of foreign investors in the process and the simplification of sale procedure. As a result of economic transition both the industrial and the agricultural production decreased significantly. Because of unfavourable external conditions (the collapse of Comecon) the Hungarian economy was hit by a deep recession. The prevailing economic difficulties were further exacerbated by the fact that both domestic investments and consumption declined, whereas gross government debt reached 85 per cent in the mid-1990s. Another negative outcome of the transformation process was that inflation started to accelerate, however, it was kept under control in 1997. The objective of my study is to evaluate the impacts of economic transition in Hungary between 1988 and 1998. I will focus on analysing the process of privatisation and the macroeconomic consequences of the change of regime. Because of length constraints, I will not highlight the political system after 1990. Az 1980-as évek végére az államszocialista rendszer általános válságba került Magyarországon. A pártállami vezetés felismerte, hogy a lakosság életszínvonalának növelésére és a gazdasági növekedés fenntartására tett erőfeszítések eredménytelennek bizonyultak. Az átalakulás folyamata már a rendszerváltozást megelőző években elindult, így hazánkban átfogó gazdasági reformintézkedéseket fogadtak el az 1980-as évek második felétől. A többi szocialista országhoz hasonlóan a gazdasági átalakulás kedvezőtlen hatást gyakorolt mind az ipari, mind pedig a mezőgazdasági termelésre. A KGST megszűnése miatt Magyarország elvesztette hagyományos piacait. A gazdasági nehézségeket tovább súlyosbította a beruházások és fogyasztás visszaesése, miközben az államadósság – a Kádár-korszak örökségeként – az 1990-es évek közepére elérte a bruttó hazai termék 85 százalékát. Az átalakulási folyamat további negatívuma volt az infláció felgyorsulása. A fogyasztói árszínvonal növekedését csak 1997-ben sikerült megállítani. Tanulmányom célja a gazdasági átalakulás eredményeinek rövid bemutatása az 1988 és 1998 közötti időszakban. Vizsgálódásom középpontjában a privatizáció mellett a rendszerváltozás gazdasági következményeinek elemzése áll. Ugyanakkor terjedelmi korlátok miatt tanulmányomban nem kívánok foglalkozni az 1990 utáni politikai rendszerrel.